2019
DOI: 10.1111/brv.12516
|View full text |Cite
|
Sign up to set email alerts
|

Two potential evolutionary origins of the fruiting bodies of the dictyostelid slime moulds

Abstract: Dictyostelium discoideum and the other dictyostelid slime moulds (‘social amoebae’) are popular model organisms best known for their demonstration of sorocarpic development. In this process, many cells aggregate to form a multicellular unit that ultimately becomes a fruiting body bearing asexual spores. Several other unrelated microorganisms undergo comparable processes, and in some it is evident that their multicellular development evolved from the differentiation process of encystation. While it has been arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 146 publications
(200 reference statements)
0
3
0
Order By: Relevance
“…When the life cycles of Dictyostelids and myxogastrids are compared, the presence of diploid zygotes makes it reasonable to infer that the plasmodial cycle of myxogastrids is comparable to the sexual cycle of Dictyostelids, rather than to the multicellular cycle (see [ 45 , 46 ] for more discussions on this point).…”
Section: A Parallel World Of Multicellular Complexity: the Evolution Of Social Amoebasmentioning
confidence: 99%
“…When the life cycles of Dictyostelids and myxogastrids are compared, the presence of diploid zygotes makes it reasonable to infer that the plasmodial cycle of myxogastrids is comparable to the sexual cycle of Dictyostelids, rather than to the multicellular cycle (see [ 45 , 46 ] for more discussions on this point).…”
Section: A Parallel World Of Multicellular Complexity: the Evolution Of Social Amoebasmentioning
confidence: 99%
“…When the life cycles of Dictyostelids and myxogastrids are compared, the presence of diploid zygotes makes it reasonable to infer that the plasmodial cycle of myxogastrids is homologous to the sexual cycle of Dictyostelids, rather than the multicellular cycle (see [39,40] for more discussions on this point).…”
Section: "Social Amoebas" In Amoebozoathe Phylogenetic Contextmentioning
confidence: 99%
“…Myxomycetes are a protist group belonging to the Eumycetozoa ( Kang et al, 2017 ; Hehmeyer, 2019 ). They have played a crucial ecological role in terrestrial habitats and some of those metabolites have also been demonstrated to exhibit antitumor activity, antibacterial activity, and antioxidant activity ( Keller & Everhart, 2010 ; Li et al, 2022 ; Wang, Li & Liu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%